2003
DOI: 10.1023/a:1023470921116
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Hyperglycaemia reduces proliferation of bovine aortic endothelial cells in vitro. A similar effect in vivo may contribute to long-term complications of diabetes such as impaired wound-healing and retinopathy. We report the effect of increased glucose concentrations, glycated basic fibroblast growth factor (FGF-2) and bovine serum albumin-derived advanced glycation endproducts (BSA-AGE) on the proliferation of bovine aortic endothelial cells. Glucose (30 and 50 mmol/l) had an antiproliferative effect on endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…One therapeutic approach suggested to reduce postprandial hyperglycemia is by the inhibition of two key enzymes linked to type 2 diabetes mellitus, namely α-glucosidase and α-amylase, in the digestive organs [9]. Recently, it has been reported that compounds with combined antioxidant potential and antiglycation properties are effectively used to treat diabetes mellitus [8].…”
Section: Introductionmentioning
confidence: 99%
“…One therapeutic approach suggested to reduce postprandial hyperglycemia is by the inhibition of two key enzymes linked to type 2 diabetes mellitus, namely α-glucosidase and α-amylase, in the digestive organs [9]. Recently, it has been reported that compounds with combined antioxidant potential and antiglycation properties are effectively used to treat diabetes mellitus [8].…”
Section: Introductionmentioning
confidence: 99%
“…[18] However, although numerous AGE inhibitors, including the well-known aminoguanidine, ameliorated diabetic complications in an animal model, they also caused severe side effects including gastrointestinal disturbance, anemia, and flu-like symptoms. [19] Natural products represent an important option for the discovery and development of new anti-AGE pharmaceuticals; these can include metabolites with antioxidant activity since oxidative stress is involved and accelerates the formation of AGEs.…”
Section: Introductionmentioning
confidence: 99%
“…The FRAP assay measures the ability of antioxidants to reduce ferric ion in the complex [Fe(III)(TPTZ) 2 ] 3+ to [Fe(II)(TPTZ) 2 ] 2+ through electron transfer and cannot detect compounds that act by HAT (Duraisamy et al. 2003 ; Prior et al. 2005 ; Craft et al.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds offering both properties have been reported to show greater efficacy for treating diabetes mellitus versus compounds targeting an individual pathway (Duraisamy et al. 2003 ). As such, on-going screening of natural compounds that offer combined antioxidant and anti-glycation properties with relatively low toxicity are promising candidates for the development of functional additives aimed at reducing protein glycation for the treatment and management of oxidative stress-related diseases, diabetic complications and other AGE-associated diseases (Elosta et al.…”
Section: Introductionmentioning
confidence: 99%